Challenges and opportunities to develop Kazakhstani logistics projects within the BRI - Hans-Christian Brauweiler; Aida Yerimpasheva (OrdnungsPolitisches Portal (OPO), 2022)
The BRI initiative presents a colossal opportunity for landlocked Kazakhstan to become a central logistics hub. However, this prospect is overshadowed by geopolitical risks that have escalated since the beginning of 2022. The Ukrainian crisis increased geopolitical tensions on the Eurasian continent and worldwide. Furthermore, it disrupted respectively delayed logistics, as the borders both between Russian Federation and Belarussia on one side and many nations in Europe were practically closed, air traffic has to take huge diversions, increasing time and costs for the freight. A full-scale crisis has global consequences for states and people. Western companies have stopped their activities in Russia. Western countries have imposed unprecedentedly harsh sanctions on Russia. Supply chains can be broken. Chinese companies are concerned that their goods may be stopped at the border between Russia and the countries of Central and Eastern Europe. Because of close economic and political ties with the Russian Federation and membership in the Eurasian Economic Union (EAEU), Kazakhstan is concerned with secondary sanctions. Actually, there is already some impact, as Russian Banks in Kazakhstan have to cope with difficulties in international payments, which rebounds to their (innocent, kazakh and international expatriate) customers. Companies face a particular business risk that can be referred to as "geopolitical risk." Geopolitical risks are becoming the main problem for the further development of the Eurasian region.
Keywords: 330; logistics; hub; geopolitical risks; projects; EAEU; BRI; SREB; cooperation; transport logistics complex